2-Formylpyrroles as Building Blocks in a Divergent Synthesis of Pyrrolizines - Martínez-Mora, Eder I.; Caracas, Miguel A.; Escalante, Carlos H.; Espinoza-Hicks, Carlos; Quiroz-Florentino, Héctor; Delgado, Francisco; Tamariz, Joaquín (Synthesis, 2016)
The selective functionalization of 2-formylpyrrole to provide diverse 1,2- and 1,2,5-substituted pyrroles is described. These compounds were used as versatile building blocks in a divergent synthesis of biologically valuable aza-bycyclic skeletons, such as pyrrolizine and pyrrolizidine derivatives. These bicycles were prepared following metal-free cascade synthetic approaches via regioselective intramolecular 1,3-dipolar cycloadditions and stereoselective Knoevenagel/Michael/ cyclization with dimethyl malonate.
Keywords: 2-formylpyrrole; pyrrolizines; pyrrolizidines; cascade reactions; Knoevenagel/Michael/cyclization